Mapping local structural perturbations in the native state of stefin B (cystatin B) under amyloid forming conditions - Paramore, Robert; Morgan, Gareth J.; Davis, Peter J.; Sharma, Carrie-anne; Hounslow, Andrea M.; Taler-Vercic, Ajda; Zerovnik, Eva; Waltho, Jonathan P.; Cliff, Matthew J.; Staniforth, Rosemary A. (Frontiers in Molecular Neuroscience, 2012)
Unlike a number of amyloid-forming proteins, stefins, in particular stefin B (cystatin B) form amyloids under conditions where the native state predominates. In order to trigger oligomerization processes, the stability of the protein needs to be compromised, favoring structural re-arrangement however, accelerating fibril formation is not a simple function of protein stability. We report here on how optimal conditions for amyloid formation lead to the destabilization of dimeric and tetrameric states of the protein in favor of the monomer. Small, highly localized structural changes can be mapped out that allow us to visualize directly areas of the protein which eventually become responsible for triggering amyloid formation. These regions of the protein overlap with the Cu (II)-binding sites which we identify here for the first time. We hypothesize that in vivo modulators of amyloid formation may act similarly to painstakingly optimized solvent conditions developed in vitro. We discuss these data in the light of current structural models of stefin B amyloid fibrils based on H-exchange data, where the detachment of the helical part and the extension of loops were observed.